Key building blocks for high-capacity WDM photonic transport networks. - Jourdan, A. (IEEE Journal on selected areas in communications)
The objective of this paper is to give an overview of the different studies we have performed at the research level regarding the design and implementation of a photonic wavelength division multiplexing (WDM) layer providing transparent transport services to client layers (SONET/SDH, ATM, etc.). Such a network requires a number of enabling factors to be assessed in order to become a reality. Among these factors are the availability of high-capacity WDM transmission systems and efficient optical routing nodes based on mature technology, the design of robust networks optimizing the utilization of resources, and the development of a management system in accordance with presently applied standards for transport networks. We review our achievements in these different fields